Complement evasion strategies of Borrelia burgdorferi sensu lato. Issue 16 (11th August 2020) - Dulipati, Vinaya; Meri, Seppo; Panelius, Jaana
Abstract : Borreliosis (Lyme disease) is a spirochetal disease caused by the species complex of Borrelia burgdorferi transmitted by Ixodes spp. ticks. Recorded to be the most common tick‐borne disease in the world, the last two decades have seen an increase in disease incidence and distribution, exceeding 360 000 cases in Europe alone. If untreated, infection may cause skin symptoms, arthritis, and neurological or cardiac complications. Borrelia spirochetes have developed strategies to evade the mammalian host immune system. These include the complement system, which is an important first‐line defense mechanism against invading microbes. To evade the complement, spirochetes bind soluble complement regulators factor H (FH), factor H‐like protein, and C4bp to their outer surfaces. B. burgdorferi spirochetes can inhibit the classical pathway of complement by the outer surface protein (Osp) BBK32, which blocks the activation of the C1 complex, composed of C1q, C1r, and C1s. The FH‐binding proteins of borreliae include Osps OspE, CspA, and CspZ. Following repeated infections, antibodies against these proteins develop and may provide functional immunity against borreliosis. This review discusses critical immune evasion strategies, focusing on complement evasion by borreliae. Abstract :